Flood planning the politics of water security - Warner, Jeroen (International library of political studies, 2011)
Floods are amongst the most common and devastating natural disasters. In the wake of such an event, the pressure to initiate flood protection schemes that will provide security is enormous, and politicians promise quick solutions in the national interest. The author shows how such projects inevitably become politicized as different stakeholders seek to promote their interests.